Two level reform game problems of Greece - Martha Kontodaimon; Bernhard Neumärker (University of Freiburg, Institute for Economic Research, Department of Economic Policy and Constitutional Economic Theory, 2015)
[Introduction] Contracts, may they be bilateral or multilateral, are formed with contemporary facts in mind. The contracting parties, aiming to an agreement, and wanting to cover their needs, define rules that define the essence of the relationship that is to be formed. Aiming for maximum utility they cover as many aspects of affiliation and any respective cooperation. Still, no matter how well thought or mapped, a contract my become nuance by the pass of time or an unexpected event. This contingency may lead towards inefficiency of its rules and the need of its reform. The social contract of a nation – otherwise known as its constitution -, being incomplete by nature, will be the first institution to face the need of a reform if the existing variables change. Within the constitutional economics framework, which identifies the social contract rules to have been built under a unanimous agreement, the tools and guidelines for this initial contracts reform are provided by the institution itself. Still, even if the knowledge exists, and the elasticity or inelasticity of a law is predefined, reforms that may be seen, by the impartial observer, as an improvement on the society's welfare are not immediately realized. The focus of this paper is to map the timing of an already delayed national reform, recognized as publicly beneficial, and how it can be affected by external influence under negotiation. As an external influence we identify the provision of aid coming in the country from the international sector, who by assumption here aims to support the national reform. The actors of this conflict game are heterogeneous social, national and international, groups of power influenced by their respective utilities and the negotiations occurring, simultaneously, by the two sides. [...]
Keywords: 330